Differential Cross Sections For E+-H Scattering at Intermediate Energies - M.Z.M, Kamali; K.K, Rajagopal; Kuru, Ratnavelu, (Malaysian Journal of Science, 2002)
The coupled-channel optical method (CCOM) has been used to study positron scattering by atomic hydrogen. Nine-state (H(1s), H(2s), H(2p), H(3s), H(3p), H(3d), Ps(1s), Ps(2s), Ps(2p)) and six- state basis set (H(1s), H(2s), H(2p), Ps( 1s), Ps(2s), Ps(2p)) and the continuum optical potential has been used in our calculations. We present our results for the differential cross section (DCS) for the 1s-1s, 1s-2s and 1s-2p transitions at 50, 100 and 200 eV.